Enhancing of a wind power system control using intelligent artificial control and multilayer inverter - Chandad, Abdelmoumen; Hamouda, Messaoud; Benharir, Nedjadi; Bouzidi, Mohammed (International Journal of Power Electronics and Drive Systems (IJPEDS), 2024)
The improvement of overall power quality and optimal control of reactive and active power are issues that have attracted many researchers. The harmonic is considered a main stressful source for energy quality. This paper proposed the ability of artificial intelligence at controlling the active and reactive power and to reduce torque ripple and current harmonics thus improve energy quality and the stability of system, that by using the artificial intelligence controller and a neural network based space vector modulation with two levels inverter (NSVM-2L). These inverter hold the offer improved efficiency and have on account of their capability of high voltage operation compared with traditional inverters as reducing the harmonic. These results showed that the fuzzy logic controller's dynamic performance is very superior to that of the PID controller of DFIG. The fuzzy controller works well for helping us to minimize the rate of harmonic distortion of absorbed currents and for correctly adjusting active and reactive power and its stability of wind turbine compared to PID controller.